Historical University of Latvia student solitary confinement cell: video - Rubenis, Rūdolfs; Briška, Kristaps; Damberga, Andra (LU Muzejs, 2021)
The University of Latvia has 19th-century historical witness regarding the daily life of students during studies - the historical student solitary confinement cell. The origins of the student solitary confinement cell are found in medieval Germany, when universities were entitled to turn students into cells for the misdeeds during the studies. The idea was realized in the 19th century, which coincided with the time when German academic influence spread in the Baltics. During the occupation of the USSR, this history phenomenon was forgotten or distorted, but it is now rehabilitated. The Museum of the University of Latvia has filmed a video with subtitles in English about the student solitary confinement cell, which introduces everyone with this forgotten history page in the history of Latvia's higher education.

Latvijas Universitātē atrodās 19. gs. vēstures liecinieks par studentu ikdienas dzīvi studiju laikā - vēsturiskais Studentu karceris. Studentu karcera aizsākumi meklējami viduslaiku Vācijā, kad universitātēm bija tiesības ieslēgt studentus cellēs par izdarītajiem pārpākumiem studiju laikā. Ideja realizējās 19. gs., kas sakrita ar laiku, kad vācu akadēmiskā ietekme izplatījās arī Baltijā. PSRS okupācijas laikā šis vēstures fenomens tika aizmirsts vai sagrozīts, taču tagad tas ir reabilitēts. LU Muzejs ar LU Akadēmisko apgādu ir izdevis bukletu par LU vēsturisko Studentu karceri, kas ļauj iepazīties ikvienam interesentam par šo aizmirsto vēstures lappusi Latvijas augstākās izglītības vēsturē.
Latvijas Universitātes vēsturiskais studentu karceris: video
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects; Studentu Karceris; Latvijas Universitāte; Rīgas Politehnikums/Rīgas Politehniskais institūts; Studenti; Student solitary confinment cell; University of Latvia; Riga Politechnikum/Riga Polytechnical institute; Students